Relationship between brain iron deposition and mitochondrial dysfunction in idiopathic Parkinson's disease - Jannik Prasuhn; Martin Göttlich; Friederike Gerkan; Sofia Kourou; Britt Ebeling; Meike Kasten; Henrike Hanssen; Christine Klein; Norbert Brüggemann (BMC, 2022)
Abstract Background The underlying pathophysiology of Parkinson's disease is complex, involving different molecular pathways, including brain iron deposition and mitochondrial dysfunction. At a molecular level, these disease mechanisms are likely interconnected. Therefore, they offer potential strategies for disease-modifying treatments. We aimed to investigate subcortical brain iron deposition as a potential predictor of the bioenergetic status in patients with idiopathic Parkinson's disease. Methods Thirty patients with idiopathic Parkinson's disease underwent multimodal MR imaging (T1, susceptibility-weighted imaging, SWI) and 31phosphorus magnetic resonance spectroscopy imaging. SWI contrast-to-noise ratios served as a measure for brain iron deposition in the putamen, caudate, globus pallidus, and thalamus and were used in a multiple linear regression model to predict in-vivo energy metabolite ratios. Results Subcortical brain iron deposition, particularly in the putamen and globus pallidus, was highly predictive of the region-specific amount of high-energy-containing phosphorus metabolites in our subjects. Conclusions Our study suggests that brain iron deposition but not the variability of individual volumetric measurements are highly predictive of mitochondrial impairment in vivo. These findings offer the opportunity, e.g., by using chelating therapies, to improve mitochondrial bioenergetics in patients with idiopathic Parkinson's disease.